2020
DOI: 10.1186/s13756-020-0693-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hand hygiene facilities and staff compliance in a large tertiary health care facility in northern Nigeria: a cross sectional study

Abstract: Background: The burden of healthcare-associated infection (HAI) is 2 to 18 times higher in developing countries. However, few data are available regarding infection prevention and control (IPC) process indicators in these countries. We evaluated hand hygiene (HH) facilities and compliance amongst healthcare workers (HCW) in a 600bed healthcare facility in Northcentral Nigeria providing tertiary care service for a catchment population of about 20 million. Methods: An in-house facility assessment tool and the Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
29
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 37 publications
8
29
6
Order By: Relevance
“…And those who practice ABHS often, sometimes, seldom, or never (received 0 point) and responded <50% correctly (always) were considered as non-compliant. 17 , 18 , 20–23 , 25 , 26 …”
Section: Methodsmentioning
confidence: 99%
“…And those who practice ABHS often, sometimes, seldom, or never (received 0 point) and responded <50% correctly (always) were considered as non-compliant. 17 , 18 , 20–23 , 25 , 26 …”
Section: Methodsmentioning
confidence: 99%
“…[ 21 ] Participants (40%) used common towels, 58% used personal hankerchief which was not a good practice, 33.3% used disposable paper towels, and 12.4% used other methods of hand drying after hand washing like letting it get dried by itself (air drying), sterile cotton swabs, aprons, curtains, and whatever available like other studies. [ 17 22 23 24 ] Reusing or sharing towels should be avoided because of the risk of cross-infection. Careful hand drying is a critical factor determining the level of bacterial transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Engdaw et al in Ethiopia reported that factors influencing hand hygiene adherence involved access to soap and water [10]. This lack of hand washing equipment is a common situation in low and middles countries [11], and that is the reason WHO recommends alcohol-based hand rub, which is easier to implement [2] [7]. Clothing requirements should be improved within the care unit, especially the wearing of rings, which can be a breeding ground for germs [12].…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed J et al recorded a rate of 12.3% in Karachi, Tang et al 11% to 36% depending on the season in a rural hospital in Niger[16] [17]. Higher rates of 31% are reported in Nigeria but still significantly lower than those reported in advanced countries such as England[11] [18]. The implementation of a multimodal strategy based on WHO recommendations will certainly improve hand hygiene adherence within the care unit, as various teams experimented[19] [20] [21][22].…”
mentioning
confidence: 99%